Pembuatan Aplikasi Pengamanan Data dengan Metode MARS - Witanto, Elizabeth Nathania; Budhi, Gregorius Satia; Purba, Kristo Radion (Jurnal Infra, 2015)
Nowadays, technology is growing rapidly and becoming more sophisticated, especially communications technology. Information can be deployed without having to meet each other. No doubt that any confidential information sent over the Internet. Through various types of information is developing techniques for damage or maintaining the security of the dissemination of information on the internet.Securing data by using cryptography is needed for sending confidential data so that not everyone can access it. Process undertaken in this study is encrypted messages with MARS method. Input in an application that is designed in the form of plaintext messages or files to be encrypted, then the key to encrypt the message. This application is made with the Java programming language using NetBeans IDE 7.4.The test results indicate that the encryption with MARS method can be performed on any type of file (example: text file, song or audio file, video file or movie, etc.). Files can be decrypted back to normal if the password is the same as the password for the encryption.